ONE DIMENTIONMECHANICAL EARTH MODEL AND FAULT STABILITY ANALYSIS AT JIREK FIELD, SOUTH SUMATRA BASIN - HADIPRATAMA, JONATHAN
The Jirek Field is one of Pertamina -basin, South Sumatra. Main reservoir in Jirek Field is Baturaja Formation which composed of limestone. This formation acts as main hydrocarbon producer in Jirek Field. There is an overpressure phenomenon in Jirek Field which influence the value of in-situ stress and fault stability in Jirek Field. The study started with analyzing the log data to obtain vertical stress (Sv) from density log, minimum horizontal (Shmin) stress obtained from leak off test data, and maximum horizontal stress(SHmax)obtained from empirical equation. Moreover, the data which have been processed, will be used to generate 1D geomechanical earth model. From that model, we analyzethe fault stability, including Slip Tendency (Ts), Dilation Tendency (Td) and Fracture Stability (Fs) based on geomechanics analysis. From the modelling which have been done, the result shows us that Jirek Field dominated by strike-slip regime. Image log shows the direction of maximum horizontalstress in Jirek Field is northeast southwest, which is similar the subduction trend at present time. Overpressure phenomenon which occurs in Gumai Formation, Baturaja Formation, and Talang Akar Formation generate a change of maximum horizontal stress and minimum horizontal stress value. Furthermore, overpressure phenomenon causes the stress condition of Jirek Field became shifted to the left and closer to failure envelope in Mohr diagram. Slip Tendency (Ts), Dilation Tendency (Td), and Fracture Stability (Fs) analysis concludes that fault with north west south east orientation has small sensitivity to present in situ stress (potential as seal based on geomechanics analysis). At thesame time, fault with north northwest south southeast, northwest west south east east, and southwest west northeast east has bigger sensitivity to present in situ stress. fault with northeast southwest orientation is the biggest sensitivity to present insitu stress (potential as updip migration pathway based on geomechanics analysis).